A comparison of intramuscular dexmedetomidine and intramuscular ketamine for premedication in pediatric anesthesia: a double blind randomized clinical trial - Bhandari, Sabin; Bhattarai, Balkrishna; Sah, Birendra Prasad; Subedi, Ashish; Poudel, Prakash; Prasad, Jagat Narayan (Journal of Chitwan Medical College, 2017)
Abstract on the PDF